2004
DOI: 10.1007/s10126-003-0005-9
|View full text |Cite
|
Sign up to set email alerts
|

Tensile and Tear Strength of Carrageenan Film from Philippine Eucheuma Species

Abstract: The tensile and tear strength of carrageenan film from Philippines Eucheuma species were investigated using NEC tensilon universal-testing machine according to American Society for Testing Materials methods. These properties are important for assessing carrageenan film as packaging material. The kappa and iota types were used in the study. The effect of glycerine on the tensile and tear strength including elongation was also evaluated. Addition of glycerine tended to lower the tensile strength of the film and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 1 publication
1
8
1
Order By: Relevance
“…The contrast between the WVP properties of KAPPA and HYBRID films suggests that film morphology, and in particular rice starch crystals are related to WVP: for all compositions, KAPPA films show smaller crystals and thus offer an improved tortuosity for water molecules permeating the film . Hydrocolloid films are usually characterized by their good gas barrier properties but poor water vapor permeabilities . Compiled WVP data in Table indicate that KAPPA and HYBRID films show WVP values similar to most of films made from natural polymers, with the exception of whey protein which roughly shows a tenfold larger WVP.…”
Section: Resultscontrasting
confidence: 81%
“…The contrast between the WVP properties of KAPPA and HYBRID films suggests that film morphology, and in particular rice starch crystals are related to WVP: for all compositions, KAPPA films show smaller crystals and thus offer an improved tortuosity for water molecules permeating the film . Hydrocolloid films are usually characterized by their good gas barrier properties but poor water vapor permeabilities . Compiled WVP data in Table indicate that KAPPA and HYBRID films show WVP values similar to most of films made from natural polymers, with the exception of whey protein which roughly shows a tenfold larger WVP.…”
Section: Resultscontrasting
confidence: 81%
“…-Carrageenan, which is commonly used as a gelling and stabilizing agent in food applications, is also known to have good film forming ability (Briones et al, 2004). The dependency of thecarrageenan sol-gel transition temperature on the potassium (K + ) ion has been well known since the 1980s (Rochas & Rinaudo, 1980;Rochas & Rinaudo, 1982;Rochas & Rinaudo, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…From the result, the tensile properties were represented by TS, E and YM and the water properties represented by WVP. 18,21,22 It was also observed that the TS of the composite films increased with the seaweed/starch blend ratio from 50:50 to 90:10 (SE: CS). This also indicated the improvement of TS of the films with the increase of SE content in the films.…”
Section: Mechanical Propertiesmentioning
confidence: 87%
“…It is known that a more flexible material has a lower YM, indicating that the material has higher ability to be deformed with less force. 22 The YM values of this stage ranged from 3.02 MPa to 14.20 MPa. Although the effect of blend ratio has no effect on the YM results of the composite films, the YM result of the control CS film which was 14.20 MPa was relatively higher than the films containing SE that were within 3.02 MPa to 4.63 MPa, regardless of the variation of blend ratio.…”
Section: Mechanical Propertiesmentioning
confidence: 90%